College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter 1 - Section 1.3 - Complex Numbers; Quadratic Equations in the Complex Number System - 1.3 Assess Your Understanding: 23

Answer

37

Work Step by Step

Recall, $i=\sqrt{-1}$, so $i^{2}=-1$. Thus, using the distributive property, we obtain: $(-6+i)(-6-i) =-6*-6+6i-6i-i*i =36+6i-6i-i^{2} =36-(-1) =37$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.